HUBUNGAN ANTARA DUKUNGAN EMOSIONAL DENGAN KEPATUHAN DIET LANSIA PENDERITA HIPERTENSI - Dita Rahmatika (Universitas Airlangga, 2019)
Hypertension is a condition where a person's blood pressure reaches 140/90 mmHg. Hypertension is the silent disease that causes death in Indonesia. Elderly people mostly suffer from hypertension. This study aims to investigate the correlationof emotional support and dietary compliance of elderly patients with hypertension around the area of Sukomulyo Community Health Center, Manyar subdistrict, Gresik. This study was an observational analytical research, based on the data collection.This research employed a cross sectional method. The samples used simple random sampling with a sample size of 37 respondents who were elderly patients with hypertension. The respondents’ characteristicswere mostly female with the age criteria of 60- 70 years old, and working as housewives. Meanwhile, the characteristics based on education level suggested that more than half of the respondents were high school graduates. Almost all respondents got emotional support with good category (83.8%), and most respondents were quite obedient in doing diet reaching 67.6%. The result of statistical test of the correlation between emotional support andthe adherence of elderly diet of hypertension show a p-value of 0.552.There is no correlation between family emotional support and the compliance of elderly diet in hypertensive patients in the integrated health postof elderly in the working area of Sukomulyo Community Health Center. The elderly’s family is expected to provide more attention to the elderly to be obedient in having the hypretensive diet.